Investigation of Causal Effect of Type 2 Diabetes Mellitus on Lung Cancer: A Mendelian Randomization Study - Hong, Tongtong; Qin, Na; Zhao, Xiaoyu; Wang, Cheng; Jiang, Yue; Ma, Hongxia; Dai, Juncheng (Frontiers in Genetics, 2021)
Background: Although several observational studies have attempted to investigate the association between type 2 diabetes mellitus (T2DM) and lung cancer risk, the results are controversial. Here, we intended to examine whether there is a causal association between T2DM with lung cancer risk. Materials and Methods: We conducted a Mendelian randomization study to systematically investigate the effect of T2DM on lung cancer among 13,327 cases and 13,328 controls. A weighted genetic risk score (wGRS) was constructed as a proxy instrument by using 82 previously reported T2DM-related single nucleotide polymorphisms (SNPs). The logistic regression model was utilized to estimate associations of T2DM-related SNPs and wGRS with lung cancer risk. Sensitivity analyses were also performed to assess the robustness of the observed associations. Results：We found no evidence for a causal relationship between T2DM and lung cancer risk (odds ratio, OR=0.96, 95% confidence interval: 0.91-1.01, P=0.96), and the association didn’t vary among populations of different age, sex, smoking status, and histological type. Sensitivity analyses (e.g., MR-Egger test) suggested that pleiotropic effects did not bias the result. Conclusion: Our findings indicate that no causal relationship between T2DM and lung cancer. The associations observed in previous observational studies may be attributed to confounding factors or reverse causality.